2005
DOI: 10.1074/jbc.m504548200
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like Kinase 1-mediated Phosphorylation Stabilizes Pin1 by Inhibiting Its Ubiquitination in Human Cells

Abstract: The Polo-like kinase 1 (Plk1) is a key regulator of mitosis. It is reported that the human peptidyl-prolyl cis/trans-isomerase Pin1 binds to Plk1 from mitotic cell extracts in vitro. Here we demonstrate that Ser-65 in Pin1 is the major site for Plk1-specific phosphorylation, and the polo-box domain of Plk1 is required for this phosphorylation. Interestingly, the phosphorylation of Pin1 by Plk1 does not affect its isomerase activity but rather is linked to its protein stability. Pin1 is ubiquitinated in HeLa S3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 58 publications
3
78
0
1
Order By: Relevance
“…76,77 Moreover, phosphorylation events regulate both its nuclear localization and substrate binding capability (reviewed in Wulf et al 59 ), while recently its ubiquitin-mediated degradation has been found to be inhibited by mitotic signals through Polo-like Kinase1 (Plk1). 78 Plk1 is overexpressed in many tumors and this may contribute to the increased levels of Pin1 observed in several cancers. Deregulation of Pin1 can therefore contribute to cancer progression, but this must be reconciled with its role as a regulator of p53 and p73.…”
Section: The Prolyl Isomerase Pin1mentioning
confidence: 99%
“…76,77 Moreover, phosphorylation events regulate both its nuclear localization and substrate binding capability (reviewed in Wulf et al 59 ), while recently its ubiquitin-mediated degradation has been found to be inhibited by mitotic signals through Polo-like Kinase1 (Plk1). 78 Plk1 is overexpressed in many tumors and this may contribute to the increased levels of Pin1 observed in several cancers. Deregulation of Pin1 can therefore contribute to cancer progression, but this must be reconciled with its role as a regulator of p53 and p73.…”
Section: The Prolyl Isomerase Pin1mentioning
confidence: 99%
“…For example, the E3 ligase activity of EEL-1 could be controlled by phosphorylation, as in case of the Hect E3 ligase Itch (Gao et al, 2004). Alternatively, ubiquitin-dependent degradation of a protein can be enhanced or suppressed by its phosphorylation (Musti et al, 1997;Deng et al, 2004;Eckerdt et al, 2005;Nishi and Lin, 2005;Stitzel et al, 2006). Either of these hypotheses could explain spatially restricted activity at one stage, but uniform activity at a slightly later stage.…”
Section: Research Articlementioning
confidence: 99%
“…Cette phosphorylation ne régule pas l'activité de Pin1, mais sa stabilité, en inhibant son ubiquitination et sa dégradation par le protéasome. En effet, la déplétion de PLK1 dans des cellules cancéreuses humaines entraîne l'ubiquitination et la dégradation de Pin1 [29]. Les études citées précédemment ont permis d'identifier plusieurs mécanismes de régulation de Pin1, mais il reste primordial de continuer ces investigations pour comprendre plus finement comment Pin1 est régulée afin d'identifier de nouvelles pistes thérapeutiques pour inhiber Pin1 dans les cancers humains.…”
Section: Référencesunclassified